Media Literacy Education in Cyberspace A case study of Canadian website “Media Smarts” and Iranian website “Media Literacy” - Alireza Hoseyni Pakdehi; Hosnieh Al-sadat Shobeyri (مطالعات رسانه‌های نوین, 2017)
In different countries, media literacy education methods and success rates differ. For example, Canada, with its profound history in media literacy education, is the most successful country in the world, but despite widespread importance of media in Iran, media literacy education in this country is relatively new.The present study compared performance of a model country in teaching media literacy (Canada) with a country new on this way (Iran). Therefore, the performance of Canadian Media Awareness Network that provides media literacy education via “Media Smarts Website” and Iranian “Media Literacy Website”, the only Persian website providing media literacy education, were compared using “content analysis" method. The main results are as follows: majority of the contents in Iranian Website were "informative" and "alarming", but most of the contacts in Canadian Website had features of a real “educational sources. Canadian Website developed educational contents using the theories proposed by media literacy experts; While Iranian website has not used these valuable sources.